Boric Acid–Catalyzed Hard Carbon Microfiber Derived from Cotton as a High‐Performance Anode for Lithium‐Ion Batteries. Issue 3 (12th March 2019) - Tan, Muchu; Zhang, Weihua; Fan, Changling; Li, Lingfang; Chen, Han; Li, Rong; Luo, Ting; Han, Shaochang
Abstract : The catalysis role of boric acid at 800 °C is investigated in the synthesis of hard carbon from cotton. X‐ray diffraction analysis shows that d 002 decreases and the size of the carbon crystal increases, which can only be realized at a higher temperature. Boron atoms are mainly combined on the surface layer of the particle. The specific capacity of the sample with B:C = 2.5 at 30, 1500 mA g −1 increases from 381.0 and 149.7 mAh g −1 (B:C = 0) to 526.8 and 196.6 mAh g −1, respectively. It is attributed not only to the plateau around 0.1 V, which results from the intercalation mechanism between graphite layers, but also to the storage mechanism of micropores. The capacity retention in the 200th cycle at 300 mA g −1 is improved from 88.5% to 94.1%. Therefore, the carbonization process of cotton is accelerated, and the catalysis function of boric acid proves to be workable. These improvements are partially resulting from the enlargement and regular stacking of carbon layers, which can accommodate more lithium ions. As boron atoms can occupy the defect vacancy points and order, large carbon layers are formed because of the electron deficiency property and fast transfer speed of boron atoms. Abstract : Boron atom from boric acid plays a vital role in catalyzation. It accelerates the carbonization process of hard carbon from cotton, in which the crystal size increases and the layer distance drops. Then, the electrochemical performance of hard carbon anode is greatly improved. It mainly results from the intercalation mechanism of lithium ions with similar structure to graphite.